Searching for Didactical Negotiations in Mathematics Textbooks - Gandhi, Haneet; Dewan, Hriday Kant; Ahuja, Alprata (Voices of Teachers and Teacher Educators, 2018)
This article offers guidelines for an objective, systematic review of mathematics textbooks for their didactical dispositions. Based on the recommendations of the Position Paper of the National Focus Group on Teaching of Mathematics brought out by the NCERT 2006, two categories for such an analysis have been proposed. In the first category the pedagogical aspects specific for building the disciplinary understanding of mathematics have been enumerated, while the second category suggest analyzing the approaches that textbooks adopt for handling the sociopsychological concerns related to the child.